2006
DOI: 10.1007/s10571-006-9107-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nimodipine on Calcium Homeostasis and Pain Sensitivity in Diabetic Rats

Abstract: 1. The pathogenesis of diabetic neuropathy is a complex phenomenon, the mechanisms of which are not fully understood. Our previous studies have shown that the intracellular calcium signaling is impaired in primary and secondary nociceptive neurons in rats with streptozotocin (STZ)-induced diabetes. Here, we investigated the effect of prolonged treatment with the L-type calcium channel blocker nimodipine on diabetes-induced changes in neuronal calcium signaling and pain sensitivity. 2. Diabetes was induced in y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…This is in accordance with several other studies performed on DRG neurons from STZ-diabetic mice and rats, db/db diabetic mice and BB/W rats [18, 2932], and on dorsal horn neurons from lumbar L 6 –L 7 spinal cord segments from STZ-diabetic rats [19, 33]. Shutov et al [34], however, have found an increased baseline [Ca 2+ ] i in L 4 –L 6 DRG neurons from STZ-induced diabetic rats at the same time as an unaltered baseline in DH neurons, suggesting a differential effect by diabetes on primary and secondary neurons [34]. The segmental location of the neurons investigated also appear to be affected differently by diabetes as neurons with longer axons are more susceptible to neuropathic changes than neurons with shorter axons [8].…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with several other studies performed on DRG neurons from STZ-diabetic mice and rats, db/db diabetic mice and BB/W rats [18, 2932], and on dorsal horn neurons from lumbar L 6 –L 7 spinal cord segments from STZ-diabetic rats [19, 33]. Shutov et al [34], however, have found an increased baseline [Ca 2+ ] i in L 4 –L 6 DRG neurons from STZ-induced diabetic rats at the same time as an unaltered baseline in DH neurons, suggesting a differential effect by diabetes on primary and secondary neurons [34]. The segmental location of the neurons investigated also appear to be affected differently by diabetes as neurons with longer axons are more susceptible to neuropathic changes than neurons with shorter axons [8].…”
Section: Discussionsupporting
confidence: 92%
“…Steady state cytoplasmic Ca 2+ levels are elevated in peripheral neurons of rodent models of diabetic neuropathy [41, 126, 127], most likely due to a impaired regulation of Ca 2+ homeostasis by pumps in the cell membrane, ER and mitochondria that are discussed above in the context of degenerative diabetic neuropathy. Systemic delivery of agents intended to restore neuronal Ca 2+ homeostasis have been reported to ameliorate indices of hyperalgesia in models of chemotherapeutic-induced neuropathy [128] and painful diabetic neuropathy [129131], although the location and precise mechanisms of action remain to be determined.…”
Section: Role Of Calcium In Painful Peripheral Neuropathiesmentioning
confidence: 99%
“…Thus, the role of Ltype calcium channels in small (nociceptive) DRG neurons is rather great. It should be mentioned that the effect was clearly pronounced in the case of rapid application of nimodipin, but when applications were slow, changes in Ca 2+ transients were smaller and demonstrated slow dynamics [4,10]. These findings allow one to hypothesize that agents belonging to the group of dihydropyridines may be effective in the case of pain syndromes accompanying diabetic neuropathy and that L-type calcium channels play a great role in the processes of transduction of nociceptive information.…”
mentioning
confidence: 93%